PERAN ORANG TUA DALAM MENGATASI JUDI ONLINE DI DESA KOTO MASJID KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Windy Khairani; Mori Dianto; Rahmawati Wae (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the many cases of online gambling that ensnare teenagers in Koto Masjid Village, XIII Koto Kampar District. The focus of this research is based on the role of parents as: 1). Parents as educators, 2). Parents as role models, 3). Parents as companions, 4). Parents as counselors, 5). Parents as communicators, 6). Parents as friends or companions. This research uses a qualitative descriptive approach, with 2 informants, namely SI as key informants and EM as supporting informants and 1 main informant, namely RS. The instruments used are observation, interviews and document studies. Data analysis techniques used are data reduction, data presentation (data display), and conclusions. The results of this study indicate that parents have an important role in overcoming online gambling. Parents act as educators, role models, companions, counselors, communicators and friends or companions for children in overcoming online gambling so that parents are not only intimidating but also able to embrace and advise.